PENERAPAN MODEL KOOPERATIF TIPE INSIDE-OUTSIDE CIRCLE (IOC) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 79 PEKANBARU - Nindi Andrianda; Zariul Antosa; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was carried out because of the low learning outcomes of social studies of grade VB in SD Negeri 79 Pekanbaru. Minimum completeness criteria (success criteria) assignedin school that is 78, the class consist of 28 students grade VB who reached the KKM is 12 students (43%) and students who have not yet reached the KKM is 16 students (57%) with average rating of class 71,10. The purpose of this research is to improve the learning achievement of social studies of grade VB in SD Negeri 79 Pekanbaru with the implementation of the inside-outside circle (IOC) model. The result of this research shows that the average value of basic score is 71,10 an increased in cycle 1 become 77,85. In cycle 2 the average value increased become 86,96. The activity of the teacher on the first learning of the cycle 1 got was 54,17% with the less category. The second learning was 62,50% with the enough category. On the first learning of the cycle 2 teacher activity increased become75,00% with the good category,at the second learning become 87,50% with the very good category. The activity of the students on the first learning of the cycle 1 got was 54,17% with the less category.The second learning was 62,50% with the enough category.At the first learning of the cycle 2 activity of students was 70,83% with the good category and the second learning was 95,83% with the very good category. The implementation of the inside-outside circle (IOC) can improve learning outcomes from an average of 71,10 to 86,96 with the percentage 23,20%. From this research it can be concluded that implementation of the inside-outside circle (IOC) model can be improve students learning outcomes of social studies of grade VB SD Negeri 79 Pekanbaru.Keywords: Inside-Outside Circle (IOC), social studies outcomes